Water-based concurrent training improves peak oxygen uptake, rate of force development, jump height, and neuromuscular economy in young women - Pinto, Stephanie S; Alberton, Cristine L; Cadore, Eduardo L; Zaffari, Paula; Baroni, Bruno M; Lanferdini, Fábio J; Radaelli, Régis; Pantoja, Patr{\'ıcia D; Peyré-Tartaruga, Leonardo A; Schoenell, Maira C Wolf; others (The Journal of Strength & Conditioning Research, 2015)
n/a
n/a